The Role and Obstacles of Medical Personnel in the Mitigation Phase of Natural Disasters in Developing Countries: A Systematic Literature Review - Halim Rahmat Zhafran; Rachmat Setiawibawa; Anwar Kurniadi (International Journal of Education, Vocational and Social Science, 2026)
The escalation of global natural disaster threats demands resilience in health systems, particularly in developing countries (Low- and Middle-Income Countries/LMICs) that have high structural vulnerability. This study aims to systematically synthesize the latest literature on the ideal role and actual obstacles faced by medical personnel during the natural disaster mitigation phase in developing countries. This Systematic Literature Review (SLR) was conducted by adopting the PRISMA protocol. A comprehensive search was conducted through the Dimensions bibliographic database for publications published between 2023 and 2026. From a total of 194 documents identified through specific queries, a rigorous screening and eligibility evaluation process resulted in 20 key articles to be extracted and analyzed thematically. The literature synthesis identified a crucial transformation in the role of medical personnel from a curative response approach to proactive pre-disaster mitigation agents. However, the implementation of this ideal role is significantly reduced by three main types of obstacles: (1) structural obstacles in the form of the absence of a Disaster Master Plan and operational logistical limitations; (2) managerial barriers due to disorganized crisis leadership; and (3) psychological barriers, where the lack of protection guarantees reduces the willingness to respond of health workers. There is a sharp gap between mitigation expectations and actual capacity in the field. To bridge this gap, cost-effective innovative interventions are needed, such as the adoption of mobile health (mHealth) technology and the formulation of evidence-based regulations. Strengthening the national medical defense architecture in developing countries absolutely requires the institutionalization of a sustainable disaster curriculum and the holistic integration of disciplines.